Origanum dictamnus Oil Vapour Suppresses the Development of Grey Mould in Eggplant Fruit in Vitro - Stavropoulou, Andriana; Loulakakis, Konstantinos A.; Magan, Naresh; Tzortzakis, Nikos G. (My University, 2014)
Grey mould rot (Botrytis cinerea) development in vitro or in eggplant (Solanum melongena L.) fruit was evaluated after treatment with dittany (Origanum dictamnus L.) oil (DIT) and storage at 12°C and 95% relative humidity during or following exposure to the volatiles. DIT volatiles used in different concentration (0-50-100-250 L/L) and times of exposure (up to 120 h) examined the effects on pathogen development as well as fruit quality parameters. In vitro, fungal colony growth was inhibited with the application of DIT oil (during or after exposure) and/or time of application. Continuous exposure to oils reduced conidial germination and production with fungistatic effects observed in 250 L/L. In vivo, fungal lesion growth and conidial production reduced in DIT-treated fruits. Interesting, in fruits preexposed to volatiles before fungal inoculation, DIT application induced fruit resistance against the pathogen, by reduced lesion growth and conidial production. Conidial viability reduced in >100 L/L DIT oil. Fruits exposed to essential oil did not affect fruit quality related attributes in general, while skin lightness (L value) increased in 50 and 100 L/L DIT oil. The results of the current study indicated that dittany volatiles may be considered as an alternative food preservative, eliminating disease spread in the storage/transit atmospheres.
Keywords: Essential oil; Eucalyptus oil; Food preservative; Vegetable oil